ANALISIS TUJUAN JAMUAN MAKAN BERSAMA SEBAGAI SUATU METODE PENGINJILAN BERDASARKAN KISAH PARA RASUL 2:46 DI JEMAAT PAKUSARAKAN CIMAHI BANDUNG - Bistok Hasibuan; Stimson Hutagalung (Fakultas Filsafat Universitas Advent Indonesia, 2016)
In this study, the author examines with a title is Analysis of the Purpose of EatingTogether as a Method of Evangelism Based on Acts 2:46 at Pakusarakan SDAChurch, Cimahi, Bandung. This research is conducted to know whether the purposeof eating together can be used as a method of evangelism or not? The Researcher haddistributed the list of questionnaires to 30 persons of the church member with 25statements are taken from the opinions of experts.Problem identification in this study is based on four indicators of questionsnamely: first, how about the purposes of eating in the Bible?; second, how thepurposes of eating together in the early church?; third, how the connection in theservice of the need for physical and the need for spiritual and what consequences ifavoid both of them in evangelism services?Based on observation through literature books, there are four indicators that the authoroffers namely: first, the purpose of eating in the Old Testament explained as eatingfor hospitality, eating is a sign of friendship, eating is an honor. The secondindicators are about the purpose of eating in the New Testament explained as eating isan honorary, eating is a sign of fellowship, eating is part of holistic services, eating isan instrument of reach in, eating is an instrument of reach out.The third indicators are the purpose of eating together in the early Church namelyeating together is to build up brotherly love, eating is as a sign of kindness of theheart, eating is to honor the quest, eating is to tighten or to maintain the fellowship,eating is to help the needy, eating is to remember the sacrifice and the death of Jesus.The fourth indicators are about the connection in the service of the need for physical andthe need for spiritual and what consequences if avoid both of them in evangelismservices.This study is divided into two parts namely theoretical research and field research.The theory research about the purpose of eating in the Old Testament, the author foundthat eating is for hospitality; eating is a sign of friendship; eating is a sign of virtue.Then the theory research about eating in the New Testament, the author found that eatingis an honor, eating is a sign of fellowship; eating is part of holistic services, eating is atool to reach in and eating is a tool to reach out. The last theory of this study is aboutconnection in the service of physical needs and spiritual needs. The author concluded thatthe physical and spiritual needs are two types of needs that are connected to one another.Thus the service of physical needs and spiritual needs can not be ignored inevangelism service.The Research through questionnaires distributed, authors obtained the following data: 1. For the questionnaires were distributed about the purpose of eating in the OldTestament, the authors noticed that 30 respondents have a good answer.2. For the questionnaires about statement of the purpose of eating in the NewTestament, the authors noticed that 30 respondents also have a good answer.3. For the questionnaires on the purpose of eating together in the early church, 30respondents have a good answer.4. For the questionnaires about the connection in the service of the need for physicaland the need for spiritual, 30 participators also have a good answer.Thus the results of 30 respondents answer Pakusarakan church of all thestatements from each indicator are offered, the authors concluded that all therespondents have a very positive answer that the answer category is strongly agreeand agree.